Simultaneous Assay for Four Bacterial Species Including Alloiococcus otitidis Using Multiplex-PCR in Children With Culture Negative Acute Otitis Media - Kaur, Ravinder (2010)
BACKGROUND: The 3 most commonly encountered bacteria in acute otitis media (AOM) are Streptococcus pneumoniae, Haemophilus influenzae, and Moraxella catarrhalis. Conventional culture methods detect these pathogens in only 60% to 70% of cases of AOM. Alloiococcus otitidis, another potential pathogen, has often been ignored. METHODS: Tympanocentesis was performed in 97 children with AOM presenting with a bulging tympanic membrane (TM) producing 170 middle ear fluids (MEFs). S. pneumoniae, H. influenzae, M. catarrhalis, and A. otitidis were isolated in 21%, 32%, 8%, and 0% of MEFs, respectively; no otopathogen was isolated in 29% of MEFs. In nasopharyngeal cultures at the time of AOM diagnosis, 34%, 36%, 17%, and 0% and in oropharyngeal cultures, 7%, 31%, 11%, and 0% grew S. pneumoniae, H. influenzae, M. catarrhalis, and A. otitidis, respectively. No otopathogen was isolated in 23% of nasopharyngeal and 20% of oropharyngeal cultures. Multiplex polymerase chain reaction (PCR) was used to detect DNA of the 4 bacterial species in culture negative samples. RESULTS: All culture-positive MEF, nasopharyngeal and oropharyngeal samples tested were also multiplex-PCR positive, indicating the reliability of the method. Culture-negative samples of MEF from children with a bulging TM yielded S. pneumoniae, H. influenzae, M. catarrhalis, and A. otitidis DNA in 51%, 35%, 14%, and 32% of MEF, in 45%, 31%, 10%, and 9% of nasopharyngeal and in 31%, 23%, 0%, and 3% of oropharyngeal, respectively. In 9% of the cases A. otitidis DNA was found without detection of a second organism in MEF. CONCLUSIONS: Conventional culture detected otopathogens in MEF of children with a bulging TM in 71%; using multiplex-PCR, otopathogens were detected in 88% of MEF (P < 0.01). Similar improved detection of otopathogens was noted with nasopharyngeal and oropharyngeal cultures.